2015
DOI: 10.1007/s12639-015-0689-6
|View full text |Cite
|
Sign up to set email alerts
|

A survey on parasites of long-eared hedgehog (Hemiechinus auritus) in northeast of Iran

Abstract: As there appeared to be no data available on parasite infection of Hedgehogs in the region and considering the potential threat of Hedgehogs for animal and public health, the present study was carried out using biological samples and necropsy findings collected from long-eared hedgehog captured in Mashhad city in the northeast of Iran. During the study 23 dead hedgehogs were collected randomly from different regions of Mashhad County. Following autopsy of these animals, observation for enteric parasites was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…e other studies from around the world identified several other acanthocephalan species from hedgehog including Moniliformis saudis [16,17], Plagiorhynchus cylindraceus [18], Moniliformis cryptosaudi [19], and Oliganthorhynchus erinacei [20]. Unlike other isolated species of acanthocephalan from hedgehogs, in the present study, M. ingens with the ability to infect of humans was isolated.…”
Section: Discussioncontrasting
confidence: 43%
“…e other studies from around the world identified several other acanthocephalan species from hedgehog including Moniliformis saudis [16,17], Plagiorhynchus cylindraceus [18], Moniliformis cryptosaudi [19], and Oliganthorhynchus erinacei [20]. Unlike other isolated species of acanthocephalan from hedgehogs, in the present study, M. ingens with the ability to infect of humans was isolated.…”
Section: Discussioncontrasting
confidence: 43%
“…In six peer-reviewed articles, the presence, prevalence, and pathology of lungworms were reported in hedgehogs in Iran [ 43 , 44 , 45 , 46 , 47 , 48 ]. Four species of hedgehogs, including the southern white-breasted hedgehog E. concolor , the long-eared hedgehog H. auratus , the Brandt’s hedgehog Paraechinus hypomelas (Brandt, 1836), and the desert hedgehog Paraechinus aethiopicus (Ehrenberg, 1832), occur in Iran [ 7 ].…”
Section: Resultsmentioning
confidence: 99%